Interaksi antara Tingkat Ketersediaan Air dan Varietas, Terhadap Kandungan Prolin serta Pertumbuhan Tanaman Kedelai (Glycine max L. Merr) - Eko Wahono; Munifatul Izzati; Sarjana Parman (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
The Soybean production in Indonesia has decreased due to erratic weather conditions. It is necessary to plant soybeans that are tolerant to drought stress to overcome this problem. Soybean adapt to drought stress by accumulating proline to protect cells from damage. The purpose of this study was to determine the effect of water availability on growth and proline content in soybean. This study was conducted in Greenhouse Gombel Lama and Biology Laboratory Diponegoro University. The design used was a completely randomized design (CRD) with 2 factors these are the level of water availability and soybean plant variety. This research had 6 treatments and 3 replication. Data were analyzed using ANOVA, followed by Duncan's multiple range real difference test. Parameters measured were proline content and plant growth (plant height, fresh and dry weight of shoot and roots). The results show that the level of water availability affect the content of proline and growth. The lowest water availability had the highest prolin content, that was Grobogan variety with 2,15 µmol/gr of proline content while Wilis variety had 2.30 µmol/gr of proline content. The soybean plant variety not significantly affect the content of proline and plant growth, but significantly affect on plant height and number of leaves trifoliat. Grobogan variety was more adapted to drought stress than Wilis variety.Key words : proline, water availabyility, soybean, Glycine max